Negative Impact of Covid-19 on the Endocrine System (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The SARS-CoV-2 virus has rapidly spread throughout the world, causing an unprecedented pandemic. Due to the novelty of the disease, the potential impact on the endocrine systm is currently not entirely clear. It is known that the virus uses the extracellular domain of angiotensin-converting enzyme 2 (ACE-2) and the transmembrane protein TMPRSS2 to infect cells. It is assumed that the widespread expression of ACE-2 and TMPRSS2 may be the cause of various extrapulmonary complications of SARS-CoV-2, including endocrine ones. The most discussed are lesions, direct or indirect, of the endocrine pancreas, hypothalamic-pituitary-adrenal and hypothalamic-pituitary-thyroid axes, as well as possible long-term consequences associated with the function of the reproductive system. Shown that obesity and diabetes increase the risk of severe disease and mortality in COVID-19. Patients with transient hyperglycemia, as well as diabetes mellitus, have a higher risk of severe viral infection. The severity of the condition may be due to primary and secondary adrenal insufficiency of various origins. The most common consequences of the thyroid system in COVID-19 are euthyroid pathology syndrome, transient destructive thyroiditis, including subacute thyroiditis.